2008
DOI: 10.1111/j.1460-9568.2008.06037.x
|View full text |Cite|
|
Sign up to set email alerts
|

Cellular prion protein co‐localizes with nAChR β4 subunit in brain and gastrointestinal tract

Abstract: PrP(C), the cellular isoform of prion protein, is widely expressed in most tissues, including brain, muscle and gastrointestinal tract. Despite its involvement in several bioprocesses, PrP has still no apparent physiological role. During propagation of transmissible spongiform encephalopathies (TSE), prion protein is converted to the pathological isoform, PrP(Sc), in a process believed to be mediated by unknown host factors. The identification of proteins associated with PrP may provide information about both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Various groups have shown interactions between Na + /K + -ATPase and PrP C [8], [9], [42] and there have been several suggestions that the two proteins associate to form a multiprotein complex with additional partners. One such partner is suggested to be 2′,3′-cyclic nucleotide 3′-phosphodiesterase (CNP1) [69] and interestingly this protein was identified in one of our SAF preparations and was also detected in another below the level of confidence. CNP1 is a membrane bound enzyme involved in the synthesis of the myelin sheath [70] and it has been reported that CNP1 may act as an anchor for tubulin [71].…”
Section: Resultsmentioning
confidence: 87%
“…Various groups have shown interactions between Na + /K + -ATPase and PrP C [8], [9], [42] and there have been several suggestions that the two proteins associate to form a multiprotein complex with additional partners. One such partner is suggested to be 2′,3′-cyclic nucleotide 3′-phosphodiesterase (CNP1) [69] and interestingly this protein was identified in one of our SAF preparations and was also detected in another below the level of confidence. CNP1 is a membrane bound enzyme involved in the synthesis of the myelin sheath [70] and it has been reported that CNP1 may act as an anchor for tubulin [71].…”
Section: Resultsmentioning
confidence: 87%
“…These results suggest that ΔCR PrP, instead of silencing NMDA receptors like WT PrP, activates them, possibly via a physical interaction with NR2D or other channel subunits. Alternatively, ΔCR PrP could also directly or indirectly affect the activity of other ion channels, such as nAChRs (Petrakis et al, 2008; Beraldo et al, 2010), to increase neuronal excitability. A number of electrophysiological abnormalities have been reported in neurons from PrP knock-out mice (Linden et al, 2008), suggesting that PrP C might normally modulate several kinds of ion channels, a function that could be corrupted by ΔCR or other central region mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data demonstrated that PrP C is co-localized with the ␤4 subunit of nAChR in the brain and gastrointestinal tract. However, infection experiments using the Rocky Mountain Laboratory prion strain in ␤4nAChR knock-out mice demonstrated that these animals presented with the same disease incubation period when compared with controls (61).…”
Section: Journal Of Biological Chemistry 36547mentioning
confidence: 96%